2020
DOI: 10.1186/s12936-020-3106-2
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of older insecticide-treated bed nets (ITNs) to prevent malaria infection in an area of moderate pyrethroid resistance: results from a cohort study in Malawi

Abstract: Background: A previous cohort study in Malawi showed that users of new insecticide-treated bed nets (ITNs) were significantly protected against malaria compared to non-users, despite moderate levels of pyrethroid resistance among the primary mosquito vectors. The present study investigated whether ITNs that were 1-2 years old continued to protect users in the same area with moderate pyrethroid resistance. Methods: One year following a baseline cross-sectional malaria parasitaemia prevalence survey and universa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 45 publications
3
44
0
Order By: Relevance
“…However, there are also concerns on the increasing pyrethroid resistance which is likely to affect LLINs e cacy in preventing malaria parasite infection. Even though a study in Cameroon [15] as well as various studies in Malawi [16], Benin [17,18] and several countries in Africa [19] reported that LLIN still offers some protection even in areas of high pyrethroid resistance, there is need for continuous surveillance and evaluation on the effective use of LLINs distributed by the Cameroon government and its partners to reduce malaria mortality and morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are also concerns on the increasing pyrethroid resistance which is likely to affect LLINs e cacy in preventing malaria parasite infection. Even though a study in Cameroon [15] as well as various studies in Malawi [16], Benin [17,18] and several countries in Africa [19] reported that LLIN still offers some protection even in areas of high pyrethroid resistance, there is need for continuous surveillance and evaluation on the effective use of LLINs distributed by the Cameroon government and its partners to reduce malaria mortality and morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Inadequate information can lead to the improper maintenance of vector-prevention commodities, subsequently compromising their efficacy. For example, damaged bed nets with holes and improper bed net usage have been shown to lead to outcomes worse than no usage at all [ 64 , 65 , 66 ]. Some measures may also be affected by other health conditions, such as allergic reactions to insect repellent active ingredients [ 76 ], while others may be limited by cultural concerns, as demonstrated in the case of vaccination hesitancy in certain religious communities [ 81 , 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Physical deterioration [ 64 , 65 , 66 ]: Damaged bed nets have significantly reduced efficacies. Proper maintenance of bed nets is important.…”
Section: Figurementioning
confidence: 99%
“…Other observational cohorts have reported higher incidences of malaria among non-net users compared to users in areas of moderate to high pyrethroid resistance [17]. The extent of protective efficacy afforded by pyrethroid LLINs will likely reflect the strength of local vector resistance and levels of both net physical integrity and individual compliance [32,33]. However, in Côte d'Ivoire, reported LLIN usage has been low, requiring additional behavioural interventions [2,34].…”
Section: Malaria Prevalencementioning
confidence: 99%